The Future of Science Learning: Meta-Analysis of the Effectiveness of Augmented Reality in Enhancing Critical Thinking - Betty Diah Kusumaningrum; Muhammad Syaipul Hayat; Sumarno (Jurnal Penelitian Pendidikan IPA, 2025)
The development of technology has brought significant changes in the world of education, especially in the field of Natural Sciences (IPA). Critical thinking skills are becoming increasingly important in the ever-evolving information age. Along with that, the importance of education that integrates technology in science teaching is very clear. Augmented Reality (AR) is a technology that combines the real world with digital elements to create interactive and immersive learning experiences. This study evaluates the effectiveness of augmented reality in enhancing students’ critical thinking through a meta-analysis approach. A total of 8 articles that met the author's criteria published between 2019 and 2024 were analyzed using paired samples test. The results of this research show that Augmented Reality (AR) technology significantly improves students' critical thinking skills in science learning.